ANALISIS PERMAINAN BAKIAK TERHADAP KEMAMPUAN KERJASAMA ANAK USIA 5-6 TAHUN - Sry Anita Rachman; Samsul Mujtahidin (Jurnal Ilmiah Global Education, 2023)
This study aims to describe the use of Bakiak game to the ability to cooperate in the Kindergarten of PKK Sikur Barat. This research method uses descriptive research with a qualitative approach. The data was collected by using observation and interview techniques with principals and teachers in Kindergarten of PKK Sikur Barat. The data analysis technique is by collecting data, reducing data, and drawing conclusions that describe the application of clogs to the ability of children's cooperation in a game activity. The results showed that Bakiak game is one of the games used by teachers in developing one aspect of children's development, namely social emotional in terms of cooperation. And can increase children's sense of cooperation in team games, and the games are carried out as activities at the end of the theme as game activities carried out in the school's out door environment.